2009
DOI: 10.1007/s11517-009-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of friction force reduction induced by obstetric gels

Abstract: The objective of this study was to quantify the reduction of friction forces by obstetric gels aimed to facilitate human childbirth. Lubricants, two obstetric gels with different viscosities and distilled water, were applied to a porcine model under mechanical conditions comparable to human childbirth. In tests with higher movement speeds of the skin relative to the birth canal, both obstetric gels significantly reduced dynamic friction forces by 30-40% in comparison to distilled water. At the lowest movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…In the literature devoted to the subject there is a scarcity of research on benefits resulting from obstetric gel application during the delivery. However, there are studies that confirm its effectiveness in reducing friction forces in the birth canal, preventing perineal tears and shortening the second period of delivery (Riener et al, 2009;Schaub et al, 2008). The same effectiveness regarding the prevention of perineal tears during labor was shown for a substance of similar properties and producing similar effect, hyaluronic acid (Digonnet et al, 1952; , 1955;Patrini, 1956;Scarabotto & Riesco, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the literature devoted to the subject there is a scarcity of research on benefits resulting from obstetric gel application during the delivery. However, there are studies that confirm its effectiveness in reducing friction forces in the birth canal, preventing perineal tears and shortening the second period of delivery (Riener et al, 2009;Schaub et al, 2008). The same effectiveness regarding the prevention of perineal tears during labor was shown for a substance of similar properties and producing similar effect, hyaluronic acid (Digonnet et al, 1952; , 1955;Patrini, 1956;Scarabotto & Riesco, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…From a point of view of kinetics, friction forces between the child and the vaginal part of the birth canal are opposing the force of myospasms of the womb and can hinder delivery. Inside the birth canal, obstetric gel is a means of reducing friction (Riener et al, 2009;Schaub et al, 2008;Zhuk & Pekhnyo, 2009). It is worthwhile emphasizing that many pharmacologic means of reducing delivery pains and facilitating the course of delivery exist whose application was abandoned in gynecology and obstetrics as a result of complications they can cause, whereas obstetric gel does not contain active pharmaceutical substances.…”
mentioning
confidence: 99%
“…Using lubricant gel may be a possible way to reduce perineal laceration, as it aims at decreasing the friction of the vagina during childbirth through physical effects (Aquino et al, 2019; Riener et al, 2009). However, the results from Aquino et al’s review (2019) indicated that applying lubricant gel cannot reduce the incidence of perineal laceration.…”
Section: Discussionmentioning
confidence: 99%
“…Z punktu widzenia kinetyki, siły tarcia między dzieckiem i częścią pochwową kanału rodnego są przeciwstawne do siły skurczów mięśnia macicy i mogą znacznie utrudniać poród. Środkiem zmniejszającym siłę tarcia wewnątrz kanału rodnego jest żel położniczy [5,6,7]. W badaniu zastosowano środek z grupy żeli położniczych o nazwie Dianatal, zawierający w swoim składzie: glikol propylenowy, hydroksyetylocelulozę, karbomer oraz wodę oczyszczoną.…”
Section: Wprowadzenieunclassified
“…W literaturze przedmiotu niewiele jest badań nad korzyściami wynikającymi z zastosowania żeli położniczych u kobiet w czasie porodu. Istnieją jednak badania, które potwierdzają jego skuteczność w zakresie zmniejszania sił tarcia i skracania drugiego okresu porodu [6,7]. Nie ma jednak żadnych doniesień naukowych, które uwzględniałyby opinie kobiet rodzących dotyczące ewentualnych subiektywnych doznań związanych z użyciem tego preparatu (takich jak: zadowolenie z przebiegu porodu, deklarowane wyczerpanie, kontrola bólu itd.).…”
Section: Dyskusjaunclassified